Experimental investigation of tsunami bore impact pressure on a perforated seawall - Mokhtar, Zaty Aktar; Mohammed, Thamer Ahmad; Yusuf, Badronnisa; Lau, Tze Liang (Elsevier, 2019)
Catastrophic failures of many tsunami barriers along the affected coasts during the 2011 Tohoku earthquake tsunami has prompted extensive investigation into improving and revising design codes for tsunami defence structures. To date, researchers and coastal engineers are investigating to understand the failure mechanisms and to find solutions so that the structures merely remain intact in the extreme event such as tsunami. Thus, the present work is motivated to experimentally study tsunami-induced bore pressures exerted on vertical seawalls; a solid vertical wall and a porous vertical seawall that consisted of a perforated front wall and a solid rear wall. Bores with various heights and velocities were generated by using the dam-break method. A porous seawall with 20% porosity of perforated front wall was used in this study. Bore pressures exerted on the solid rear wall and chamber oscillations that occurred in the experiments were also discussed. The experimental results showed that multiple peak pressures were observed during bore run-up phase in the time series of bore impacts. A predictive equation to estimate the maximum bore pressure on a perforated seawall was developed using multiple regression analysis. The proposed equation was also compared with previous empirical formulas.